Rome and The Guidebook Tradition From the Middle Ages to the 20th Century - Blennow, Anna; Fogelberg Rota, Stefano (De Gruyter, 2019)
Almost everyone has used a guidebook, when travelling, or in the armchair at home. But how was the guidebook born? In this book, scholars from various disciplines argue that the guidebook emerged in Rome in the late Middle Ages, to form a surprisingly consistent model for guidebooks up to our time. The descriptions of must-see monuments, recommended routes, and value-laden instructions have guided travellers to Rome through more than 1000 years.